Evaluasi User Interface pada Website SMK Negeri 5 Malang menggunakan Metode Heuristic Evaluation - Rizky Ariefpambudi; Satrio Hadi Wijoyo; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
SMK Negeri 5 Malang has an official website created to help the public get the necessary information about the school. Based on an interview with one of the people in charge of the school website, Mr. Hendra Saputra, the website is known that there has never been an evaluation related to the User Interface, so there are several problems such as content and how to provide information, the interface design is less attractive. This study uses the Heuristic Evaluation method. Heuristic evaluation is a method used in carrying out usability assessments. Heuristic evaluation links several experts or experts as evaluators who can assess whether a design complies with the 10 usability principles proposed by Neilsen. Based on the results of the evaluation with 3 evaluators, there are 12 problems that have been combined and divided into 7 of 10 heuristic principles. Based on 12 problem findings The highest percentage of problems of problems is the principle of aesthetic and minimalist design (H-8) with 40% of all problems of problems. On the other hand, the heuristic principle which has the highest gravity rating on the principle of recognition rather than recall (H-6) has a gravity rating of 4 and is in the major category.